The Employee Innovation Intervening Role on Relationship between Work Engagement and Employee Performance - Agus Diyanto; Evi Susanti; Tantri Yanuar R Syah (Penerbit Kemala Indonesia, 2019)
The main objective of this study is to examine the effect of work engagement on employee performance through employee innovation as an intervening variable. 167 employees from the health and beauty retail industry in Indonesia were used as correspondent, while the WarpPLS 6.0 analysis showed that work engagement was positively related to employee innovation and performance. Other results also confirm that innovation mediates the relationship between work engagement and employee performance. Thus, the effect of performance engagement on employee performance is very good, not only by examining how work engagement affects employee performance, but also by revealing how this relationship depends on innovation.